Takwil Tradition in Malay Literary Works: Islamic Spiritual Insights in Danarto’s Nostalgia - Achmad Ubaedillah (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2004)
This article addresses the notion of the practice of allegory accomplished by Danarto, one of Indonesian writers whose literary works express much Islamic spirituality through non-Islamic characters. Like Malay Sufi writers, allegorically Danarto uses Hindu Javanese characters in his short story, Nostalgia, to express his spiritual notion. Such practice of using symbolic expression has been well known among Koran interpreters (Mufasir) and Sufi masters (Saalik) as Takwil. In this regard, Danarto expresses his spiritual account through symbolic figures used in Hindu-Javanese tradition of the Mahabharata, such as Arjuna, Kresna, Bisma, Abimanyu, and Sembadra. Different from Malay Muslim writers who used Malay Islam spiritual terms and analogies, Danarto uses those Hindu symbolic figures to express his spiritual journey rooted in Javanese culture where syncretism of various values, especially Islam, is obvious over time. His literary endeavor is part of that long tradition of Takwil practices in Malay religious works, which are substantially identified as Islamic pantheism.